Efikasi Diri Pada Istri Jamaah Tabligh - Sonya, Eva Zuleika, Aad Satria Permadi, S.Psi, MA (2016)
Jemaah tabligh is an association of some poeplo who aim to spread the godness to others by preaching wich called as khuruj. Everyone who doing khuruj will leave thir house for a few days until months to leave their familly, especially their wife and children. Than, wife of jemaah tabligh is someone who have a husband as a active jemaah tabligh especially khuruj. When the husband did khuruj programe, there are some impact will happen to his familly. There are family, environtment and economics. Because of these impacts, the wife must have confidence in the ability of it. The purpose of this research are to know how the dynamics of self-efficacy is and the factors that influence it. Researcher using the phenomenological qualitative approach with five informants as a jemaah tabligh's wife with a minimum times is 40 days khuruj an life in Surakarta. The informants in this research were selected by a purposive sampling. The result of this research indicated that the jemaah tabligh's wife has their ability after getting the social support from groups and families. It will make informants feel sincere and able to interprate khuruj that make a religious personality. Than the informants was able to prove that that's fine to let their husband leave their house for khuruj. It will be happen if the jemaah tabligh's wife has the factor. Thera are social support, ikhlas, khuruj's meaning, and religious.